2012
DOI: 10.1007/s00330-012-2573-4
|View full text |Cite
|
Sign up to set email alerts
|

Placental vascularity and resorption delay after conservative management of invasive placenta: MR imaging evaluation

Abstract: MR imaging provides useful information after conservative management of invasive placenta and may help predict delay for complete placental resorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 43 publications
2
24
1
Order By: Relevance
“…Duration of spontaneous placental regression is observed at a median of 13.5 weeks (range: 4-60 weeks) after delivery. 33) Although pelvic embolization may promote placental resorption, 92) this tendency was not observed in our experience. 93) Further studies are needed to draw definite conclusions.…”
Section: Postoperative Managementcontrasting
confidence: 39%
See 3 more Smart Citations
“…Duration of spontaneous placental regression is observed at a median of 13.5 weeks (range: 4-60 weeks) after delivery. 33) Although pelvic embolization may promote placental resorption, 92) this tendency was not observed in our experience. 93) Further studies are needed to draw definite conclusions.…”
Section: Postoperative Managementcontrasting
confidence: 39%
“…The approach varies from laparotomy to a vaginal approach. Some 68,76,87,92) have succeeded in preserving the uterus, while others 29,33,89,93,96) were obligated to perform hysterectomy. We often use metronidazole vaginal suppositories for infection prophylaxis.…”
Section: Infection and Coagulopathymentioning
confidence: 99%
See 2 more Smart Citations
“…A fluid form of gelatin sponge (i.e., slurry) can be obtained by mixing tiny cubicles with iodinated contrast material [65]. This form should be used in women with retained placenta to induce thrombosis of intervillous spaces [24,66]. The use of slurry of gelatin sponge should be avoided in other situations because of reported cases of uterine necrosis with this specific material [60,67,68], although some authors have reported safe and effective TAE with slurry [65].…”
Section: Temporary and Permanent Occluding Agentsmentioning
confidence: 96%